Pengaruh Digital Banking dan Fintech Payment terhadap Kinerja Keuangan Bank BUMN dan Bank Non-BUMN - Ananda Sulistia; Nurabiah Nurabiah (Owner : Riset dan Jurnal Akuntansi, 2026)
This study aims to analyze the effects of digital banking and fintech payments on the financial performance of banks in Indonesia and to examine differences in these effects between state-owned banks (BUMN) and non-state-owned banks (non-BUMN). This study employs a panel data regression method on banks listed on the Indonesia Stock Exchange, with a total sample of 230 observations during the study period. The overall results indicate that digital banking has a significant effect on Return on Assets (ROA), Return on Equity (ROE), and Operating Expenses to Operating Income (BOPO). In contrast, fintech payment does not have a significant effect on all proxies of financial performance. Further results show that digital banking and fintech payments do not have a significant effect on the financial performance of state-owned banks. In contrast, for non-state-owned banks, digital banking is proven to have a significant effect on all proxies of financial performance. Meanwhile, fintech payment remains insignificant in both groups. These findings indicate that the effectiveness of digital transformation is highly dependent on an organization’s ability to integrate digital resources into strategic capabilities, suggesting that ownership structure moderates the relationship between digitalization and banking financial performance. This study implies that the success of digital transformation in banking depends not merely on technology adoption but on strategic integration and internal capabilities. These findings also open opportunities for future research to examine the role of digital transformation maturity and organizational factors in moderating financial performance.